2020
DOI: 10.1016/j.mtcomm.2020.101074
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the antimicrobial performance of metallic glass composites through surface texturing

Abstract: Sergio (2020) Optimizing the antimicrobial performance of metallic glass composites through surface texturing. Materials Today Communications, 23. p. 101074.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Nevertheless, apart from thermal oxidation, there are also other feasible approaches to introduce oxide that might be adapted accordingly, e.g. anodic oxidation [43] or laser surface treatment [32,44,45].…”
Section: Discussion On This Promising Strategy and Practical Insightsmentioning
confidence: 99%
“…Nevertheless, apart from thermal oxidation, there are also other feasible approaches to introduce oxide that might be adapted accordingly, e.g. anodic oxidation [43] or laser surface treatment [32,44,45].…”
Section: Discussion On This Promising Strategy and Practical Insightsmentioning
confidence: 99%
“…The studies previously described have been mostly focused on optimizing the chemical composition of materials to control their antimicrobial effectiveness. Nevertheless, other factors, including surface morphologies [186] and oxidation [187], crystalline phases content [188] are also at work. For instance, Villapún et al [187] demonstrated that the oxidation can increase the antimicrobial performance of the Cu-based BMGs, and the improvement can be explained by the fact that interphase boundaries could constitute the easy diffusion paths for Cu ions release, while the needle-shape structure of oxides could trigger mechanosensitive channels to promote the migration of copper ions into the cell.…”
Section: Copper Based Mgs For Antibacterial Surfacesmentioning
confidence: 99%
“…The current research on metallic implants is pointing out the possibility of fine tuning the topology and chemistry of biomaterials with natural antimicrobial properties to increase effectiveness. 118,119 Thus, surface alteration of inert and antibacterial surfaces is becoming more prominent in the biomaterial community.…”
Section: Surface Modificationsmentioning
confidence: 99%